Evaluation of mobile-based public participation in China's urban planning: Case study of the PinStreet platform. (February 2021) - Wang, Xuan; Chen, Yulin; Han, Zhiyuan; Yao, Xiaoyi; Gu, Peiqin; Jiang, Yang
Abstract: With the emergence of information technology, mobile-based public participation (MPP) has been introduced into urban planning practices. How to evaluate this new approach of public participation is important for supporting decision-making process and achieving effective public participation. Integrating traditional evaluation criteria and Internet product operation strategies, this study proposes an evaluation framework for MPP, which includes seven indicators from three dimensions: preparation, process and outcome. Taking PinStreet, a widely-used MPP platform in China, as a case, this study evaluates the effectiveness of seven pilot projects with a variety of themes and scales. The evaluation results show that factors lying in the aspects of environment, participant and organizer have a significant impact on the effectiveness of MPP. Finally, policy suggestions are proposed to promote the development of MPP. Highlights: An evaluation framework for mobile-based public participation (MPP) is proposed. Seven pilot projects base on PinStreet, an emerging MPP platform in China, are studied. Government mobilization and acquaintance society largely improves the outcome of MPP. The performance of MPP is affected by the physical quality of the site as well as participants' attachment of it.